2019
DOI: 10.1108/ijaim-06-2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity and firm value: evidence from UK financial institutions

Abstract: Purpose The purpose of this paper is, first, to empirically examine whether the appointment of females (board gender diversity) to the corporate boards of UK financial institutions can improve firm value, and second, to examine whether having females on the boards of UK financial institutions can impact firm value during the pre-/post-global financial crisis periods. Design/methodology/approach The paper uses secondary data obtained from DataStream covering 63 financial institutions over a period of 12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 86 publications
(200 reference statements)
8
70
0
7
Order By: Relevance
“…Dewan direksi dengan karakteristik yang beragam dapat membawa dampak terhadap perusahaan jika dewan direksi tersebut bisa menyelaraskan sumber daya yang dimilikinya dengan lingkungan eksternal perusahaan. Keberadaan direktur wanita bisa menambah variasi dari sumber daya perusahaan dan menciptakan perspektif yang beragam tentang pengelolaan sumber daya lainnya, sehingga pengelolaan sumber daya lainnya dapat menjadi lebih efisien (Agyemang-Mintah & Schadewitz, 2017).…”
Section: Kajian Teoriunclassified
“…Dewan direksi dengan karakteristik yang beragam dapat membawa dampak terhadap perusahaan jika dewan direksi tersebut bisa menyelaraskan sumber daya yang dimilikinya dengan lingkungan eksternal perusahaan. Keberadaan direktur wanita bisa menambah variasi dari sumber daya perusahaan dan menciptakan perspektif yang beragam tentang pengelolaan sumber daya lainnya, sehingga pengelolaan sumber daya lainnya dapat menjadi lebih efisien (Agyemang-Mintah & Schadewitz, 2017).…”
Section: Kajian Teoriunclassified
“…Board diversity, for example, can assist firms in gaining different information and wider exposure to the environment from suppliers, customers, policymakers, as well as social groups and competitors (Elsharkawy, Paterson, & Sherif, 2018; Horbach & Jacob, 2018; Tingbani, Chithambo, Tauringana, & Papanikolaou, 2020). Moreover, board diversity enhances board independence and decision‐making quality as it takes the views of underrepresented groups into account (Agyemang‐Mintah & Schadewitz, 2019; Elmagrhi, Ntim, Elamer, & Zhang, 2018; Ferrero‐Ferrero, Fernández‐Izquierdo, & Muñoz‐Torres, 2015; Glass, Cook, & Ingersoll, 2016). Supporting this view, García‐Meca, García‐Sánchez, and Martínez‐Ferrero (2015) suggest that more diversity on the board helps to represent all shareholders better and promote better discussion within boardrooms.…”
Section: Introductionmentioning
confidence: 99%
“…This was followed in 2015 by Spain was 40 percent, France was 40 percent by 2016, Italy in 2015 was 33.3 percent and The Netherlands in 2016 was 30 percent (Bertoni et al;2014). The European Commission had been controlling the growth of representation of women in board in all countries that in their membership and by 2020 had set a target of 40 percent; nevertheless, no formal mandatory requirements had been established (Agyemang-Mintah & Schadewitz, 2019). Wang and Oliver (2009) showed that the ASX CG Council in Australia used the "if not, why not" approach to promote gender diversity in all Australian listed companies.…”
Section: Gender Diversitymentioning
confidence: 99%
“…For example, boards that had gender diversity might provide a lot of opinions and perspectives to discussions in boards meetings, so the board can be directed for having improved plans and better decisions. (Agyemang-Mintah & Schadewitz, 2019) According to Triki (2018), the participation of women directors in the firm's board encouraged regularly better ideas, communication and participation; therefore, gender diversity might help in serving more needs and demands of wider base of investors and other stakeholders. So, having different points of view on boards could improve the capability of the firm to serve needs of wider base of stakeholders; including stockholders, creditors, lenders, auditors, and analysts.…”
Section: Board Gender Diversitymentioning
confidence: 99%
See 1 more Smart Citation